The Influence of Brand Image, Brand Awareness, and Brand Trust on Purchase Decisions Moderated by Social Media Use at CV Produksi Median Percetakan - Al-Amin, Muhammad Surya Duta; Ambarwati, Diana; Aulia Munawaroh, Nuril (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the influence of brand image, brand awareness, and brand trust on purchase decisions, with social media use as a moderating variable in the printing industry. The research aims to analyze the direct and moderating effects of these variables on consumers of CV Produksi Median Percetakan. A quantitative approach with causal associative design was applied using SEM-PLS and SmartPLS 4.0 on 96 respondents selected through purposive sampling. The results show that brand awareness and brand trust significantly influence purchase decisions, while brand image and social media moderation are not significant. The findings highlight the importance of trust and awareness in strengthening consumer purchasing decisions.